2019
DOI: 10.1093/rheumatology/kez330
|View full text |Cite
|
Sign up to set email alerts
|

Defining remission in rheumatoid arthritis: does it matter to the patient? A comparison of multi-dimensional remission criteria and patient reported outcomes

Abstract: Objectives In a cross-sectional study, we evaluated the prevalence of ‘multi-dimensional remission’ (MDR) and its component parameters, assessed using objective measures in a cohort of RA patients in treatment-induced DAS28-remission, and their relationship with patient-reported outcome measures. We sought to confirm the feasibility and face validity of the MDR construct, providing a platform for future longitudinal studies in which its clinical utility might be further established. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…We have previously reported that when patients received steroids >3 months before their baseline visit at the IA-stage of the continuum, there was no impact on the distribution of T-cell subset frequencies 25 nor was there any significant difference in whole blood lymphocyte counts between any of the groups (data not shown).…”
Section: Quantification Of T-cell Subsetsmentioning
confidence: 89%
See 3 more Smart Citations
“…We have previously reported that when patients received steroids >3 months before their baseline visit at the IA-stage of the continuum, there was no impact on the distribution of T-cell subset frequencies 25 nor was there any significant difference in whole blood lymphocyte counts between any of the groups (data not shown).…”
Section: Quantification Of T-cell Subsetsmentioning
confidence: 89%
“…Despite low sensitivity, the high specificity of abnormal naïve T-cells (confirmed by regression modelling) allows identification of patients who should not taper therapy. Further study of the depth of remission need to be performed to assess the sustainability of remission over 12 months notably when on b-DMARDs., Recent data showing that 25-30% of patients with DMARD induced remission, present with reduced naïve cells indicates the potential of this approach 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If aiming for a state closer to normality (true remission), a concept of multi-dimensional remission (MDR) should be used, involving the achievement of different depths of remission, using clinical, imaging and additional serological, immunological or histological parameters [33]. MDR has been shown to be related to better patient-reported outcomes, although prospective data is necessary to de nitely address this issue.…”
Section: Discussionmentioning
confidence: 99%